Particulate matter and hospital admission due to arterial hypertension in a medium-sized Brazilian city - Luiz Fernando Costa Nascimento; Juliana Batrov Francisco (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
This study aims to assess the effects air pollution on hospitalization due to hypertension. An ecological study was conducted using data regarding hospitalizations due to hypertension in São José dos Campos, State of São Paulo, Brazil between January 1, 2007 and December 31, 2010. The pollutants analyzed by this study were particulate matter, sulfur dioxide and ozone. A significant association between exposure to particulate matter and hospitalization due to hypertension was identified using Poisson regression with lags of up to four days. Relative risk of hospital admission ranged between 1,009 and 1,019. A 10μg/m³ increase in concentration of particulate matter was associated with a 13% increase in risk of hospitalization.